Investigation of the mechanical and radiation shielding features for BaO-WO3-P2O5 glass systems - Sayyed, M. I.; Kumar, Ashok; El-bashir, B. O.; Mahmoud, K. A.; M. Zaid, M. H.; Sidek, A. A.; Matori, Khamirul Amin (Elsevier, 2022)
The influence of inserting WO3 in a barium-phosphate glass system (BaWP) with the chemical composition of (50-x)BaO+ (x + y)WO3 + (50-y)P2O5, where x = y and x + y = 10, 20, 30, 40, 50, and 60 mol% was evaluated. Makishima-Mackenzie's theory was applied to describe the tested BaWP glasses’ mechanical properties. The mechanical moduli (Young's, shear, bulk, and longitudinal) were predicted based on packing factor, coordination number, and the ionic radius of elements constituting the current glasses. Moreover, The shielding ability of the investigated glass samples was assessed using the Monte Carlo. The simulated results showed the best mass attenuation coefficient recorded for the BaWP7 glass sample. It is ranged between 0.3191 and 0.0517 cm2/g for gamma photons ranging from 0.284 to 1.406 MeV, respectively.